1999
DOI: 10.1068/a311473
|View full text |Cite
|
Sign up to set email alerts
|

Property Ownership, Tenure, and Displacement: In Search of the Process of Gentrification

Abstract: Despite three decades of continuous research on gentrification, there are a number of areas where understanding of this process still remains quite rudimentary, especially with respect to the actual process of gentrification itself. The author seeks to focus attention upon this issue by examining how historic change to property ownership and tenure structure of housing induced by gentrification impacted upon the unfolding of this process in the inner Sydney suburb of Glebe from 1960 to 1986. By using an empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…There have been several studies which have shown the effect of tenure conversions on stimulating gentrification (Hamnett & Randolph ; Murie ; Murie & Musterd ; Engels ; Millard‐Ball ; Kennett & Forrest ). Like much of gentrification research, these studies have a tendency to focus on social economic transformation, that is, changes in income or class over time.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies which have shown the effect of tenure conversions on stimulating gentrification (Hamnett & Randolph ; Murie ; Murie & Musterd ; Engels ; Millard‐Ball ; Kennett & Forrest ). Like much of gentrification research, these studies have a tendency to focus on social economic transformation, that is, changes in income or class over time.…”
Section: Introductionmentioning
confidence: 99%
“…Even trajectories ending with the Private Rented Sector can be understood in this way, as has been argued in studies highlighting the multiplicity of tenure trajectories in gentrifying areas (DeGiovanni and Paulson 1984;Engels 1999;Paccoud 2017). For the six tenure changes described above, Outer London upscaling outnumbers that in Inner London (324 vs 266 OAs).…”
Section: The Spatial Distribution Of Upscaling and Downscaling Linkedmentioning
confidence: 88%
“…The two study sites examined in this research were the suburb of Glebe in Sydney and the suburbs of Cooks Hill and Newcastle East in Newcastle, hereafter referred to as Inner Newcastle unless otherwise specified. These study sites were selected on the grounds that both have well documented gentrification histories (see Horvath and Engels, 1985; Engels, 1999; Rofe, 2000; 2003; 2004; Bridge, 2001). This is important because the aim of the broader research agenda was to study the emergence of the gentrifying class as an élite global community and not to study the gentrification process per se .…”
Section: Sydney and Newcastle: Local Study Sites In A Global Contextmentioning
confidence: 99%